الّأغشية الرقيقة لأكسيد القصدير المطعم بالكوبالت وتطبيقاتها - شفاء, قادي; بشرى, قادي (universty of elouedجامعة الوادي, 2020)
تم الإهتمام خلال هذا العمل بدارسة كل من الخصائص البنيوية، الضوئية و الكهربائية لأغشية أكسيد القصدير النقي (SnO2) والمطعم بالكوبالت (Co) بنسب (0، 1، 2، 3، 4 و5)% ، و ذلك إنطلاقا من مادتي كلوريد القصدير (SnCl2) و كلوريد الكوبالت (CoCl2)، يتم ترسيب المحلول على ركائز زجاجية تحت درجة حرارة 480Cº لمدة 6.5 دقائق و ذلك من خلال تقنية الرش بالإنحلال الحراري. أظهر إنعراج الأشعة السينية أن لأغشية أكسيد القصدير المطعم بالكوبالت بنية متعدد التبلوررباعي الزوايا و تأخذ إتجاهين تفضليين على التوالي(211) و (110) للنقية و المطعمة، و أبدت النفاذية الضوئية تناقصا في المجال من (%80 إلى %86)، أما المقاومة السطحية فقد شهدت إرتفاعا من 34.44Ω إلى 52.85Ωعند نسبة التطعيم 5 % و تتغير قيم الفاصل الطاقي وفقا لنسب التطعيم بالكوبالت ليأخذ القيم من 3.65eV إلى 3.89eV . In this work, we studied structural, optical and electrical characterization of undoped tin oxide (SnO2) andCobalt (Co) doped (SnO2) thin films, Which have been deposited from tin chloride (SnCl2) and Cobalt chloride(CoCl2) onto glasssubstrates by spray pyrolysis technique Samples were deposited for 6.5 minutes at the substrate temperature of 480°C. the doping concentrationof (Co) was varied from (0, 1, 2, 3, 4 and 5)% in solution. X-ray diffraction (DRX)has Shawn polycrystalline structure according to Tetragonal Rutile(SnO2) and took two favorable directions respectively (211) and (110) as preferential orientation for Cobalt (Co) doped (SnO2) thin films. The optical transmittance of (Co:SnO2) films in visible decreasing from 80% to 86%. The sheet resistance (Rsh) increased from 34.44 Ω to 52.85 Ω at 5% vaccination rate.The optical band gap (Eg) increased from 3.65 eV to 3.89 eV With increasing of the concentration of Cobalt (Co) dopants.
مذكرة تخرج ماستر فيزياء
Keywords: أكسيد القصدير(SnO2)، الرش بالانحلال الحراري، الأغشية الرقيقة، الكوبالت (Co)، إنعراج الأشعة السينية.; Tin oxide(SnO2), Spray pyrolysis, Thin films, cobalt (Co), X-ray diffraction (XRD).